2019
DOI: 10.1177/1071100719845016
|View full text |Cite
|
Sign up to set email alerts
|

MRI Assessment of Degeneration of the Tendon in Achilles Tendon Ruptures

Abstract: Background: The extent of tendinosis along the entire tendon in Achilles tendon ruptures (ATRs) has not previously been assessed. MR images of acute ATRs were evaluated to assess this extent, even in areas distant from the rupture. Methods: Patients who had MR images for an ATR were reviewed. Each tendon was divided into a proximal, middle, and distal segment with the full tendon length defined as the length measured from the myotendinous junction to the insertion. The site of tendon rupture, presence of tendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…There were 25 (53.2%) cases on the left side and 22 (46.8%) cases on the right side. The presence of tendinopathy was identified in 22 patients before the operation according to the crieteria of Bäcker et al ., 26 and all tendinopathy were visually confirmed during the operation. The average times from injury to MRI examination and surgery were 1.89 ± 2.65 and 3.81 ± 3.44 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 25 (53.2%) cases on the left side and 22 (46.8%) cases on the right side. The presence of tendinopathy was identified in 22 patients before the operation according to the crieteria of Bäcker et al ., 26 and all tendinopathy were visually confirmed during the operation. The average times from injury to MRI examination and surgery were 1.89 ± 2.65 and 3.81 ± 3.44 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A hematoma would be formed between the broken end and the retrocalcaneal tubercle. According to the MRI assessment criterion for degeneration of the tendon in ATR proposed by Bäcker et al ., 26 the signal change was assessed, and the presence of degenerative tendinopathy was recorded. In Figure 4, a case of ATR with tendinopathy at both broken ends, especially at the distal end, was presented.…”
Section: Methodsmentioning
confidence: 99%
“…Backer et al reported that the average distance of the Achilles tendon rupture is 5.86 + 2.66 cm from the calcaneal insertion. 4 Park et al observed that the average rupture site is 6.4 + 1.5 cm proximal to the calcaneal insertion. 5 These results contradicted previous reports on common rupture sites at 2-6 cm proximal to the calcaneal insertion; as such, objective imaging modalities, such as MRI or ultrasound, should be used to measure rupture sites.…”
Section: Introductionmentioning
confidence: 99%
“…8 A similar study found a mean lengthening of 15.9 mm in a group of Achilles repair patients, although the time to weightbearing once again did not predict lengthening, as the early and delayed weight-bearing groups both had elongation of the tendon. 9 Given that the mean length of the Achilles tendon is approximately 10 cm, 10 this elongation could lead to a significant loss of maximally achievable strength.…”
mentioning
confidence: 99%